Latent Profiles of Teacher-Reported Self-Regulation and Assessed Executive Function in Low-Income Community Preschools: Relations With Motor, Social, and School Readiness Outcomes - Williams, Kate E.; Bentley, Laura A. (Frontiers in Psychology, 2021)
This study contributes to understandings of early childhood self-regulation and executive function, and their components, through taking a person-centred approach to investigating how these skills cluster together in children aged 4-5 years. A sample of children (N = 206) from preschools in low socio-economic communities were assessed through teacher report of self-regulation and three executive function tasks at the commencement of the preschool year. Outcome variables included teacher report of social skills and behavioral problems, and children’s school readiness and visual motor integration skills were directly assessed. When the scores from this low-income sample were compared to available norms, over 70% of children scored below the 50th percentile in executive function measures, approximately 20% were below average in self-regulation skills, 48% were delayed in school readiness scores, 36% had above average levels of internalising problems, and 25% were above average in externalising problems. A series of four latent profile models each used different measurement approaches and combinations of self-regulation and executive function components. In three of the four models (two which combined self-regulation and executive function measures and one with teacher report of self-regulation only), a high skill and low skill profile were found with 31% to 42% of children in the low profile depending on the model. Children were very similarly classified across all three models. When three executive function scores were modelled alone a more complex three-profile solution emerged (low, moderate, high) with 52% in the low profile. Children identified in the low profiles across all models were at greater risk of poorer school readiness, visual motor integration and social skills, and increased behavioral problems. Taken together the findings suggest that self-regulation and executive function skills tend to cluster together at this age and in this low-income sample. Composite scores of teacher report of self-regulation are somewhat sufficient in identifying children who also have poorer executive function skills and are at risk of poorer motor, social, and school readiness outcomes. These children are an important target group for additional supports prior to school entry.